Barriers to entry and exit in the mobile service sector in Algeria - Ishak, Adel (Milev Journal of Research and Studies, 2023)
The aim of this study is to determine the nature of the entry barriers and the exit barriers in the mobile service sector in Algeria, this is because these barriers directly affect in the structure of the sector , especially in terms of the degree of competition in it, We found that Algeria's mobile service sector was characterized by natural entry barriers associated with economies of scale and capital requirements, as well as concentration on the research and the development which is characterized by the sector especially on the level of equipment and services. There are also legal entry barriers imposed by the ARPT, which regulate competition and grant licenses…, The legal entry barriers play a key role in influencing the degree of the competition especially in reducing the entry of new institutions. The sector also includes strategic entry barriers, particularly in the control of dealers on distribution channels in the sector. In addition to barriers to entry the sector also has barriers to exit, as the sector is provides thousands of direct and indirect jobs, and the association of the sector's institutions with other sectors, which is reflected in the various offers to institutions, the sector is also subject to the licensing system granted in person for a period of 15 years so that it may not be waived or the rights resulting there from, except with the consent of the donor body which hinders the exit from the sector .